The Effect of Lipotoxicity on Renal Dysfunction in a Nonobese Rat Model of Metabolic Syndrome: A Urinary Proteomic Approach - Markova, Irena; Miklankova, Denisa; Hüttl, Martina; Kacer, Petr; Skibova, Jelena; Kucera, Jan; Sedlacek, Radislav; Kacerova, Tereza; Kazdová, Ludmila; Malinska, Hana (Journal of diabetes research, 2019)
Introduction: The development of metabolic syndrome-associated renal dysfunction is exacerbated by a number of factors including dyslipidemia, ectopic deposition of lipids and their toxic metabolites, impairment of lipid metabolism, and insulin resistance. Renal dysfunction is also affected by the production of proinflammatory and profibrotic factors secreted from adipose tissue, which can in turn directly impair kidney cells and potentiate insulin resistance. In this study, we investigated the manifestation of renal lipid accumulation and its effect on renal dysfunction in a model of metabolic syndrome-the hereditary hypertriglyceridemic rat (HHTg)-by assessing microalbuminuria and targeted urinary proteomics. Male Wistar control rats and HHTg rats were fed a standard diet and observed over the course of ageing at 3, 12, and 20 months of age. Results: Chronically elevated levels of triglycerides in HHTg rats were associated with increased levels of NEFA during OGTT and over a period of 24 hours (+80%, P < 0.01). HHTg animals exhibited qualitative changes in NEFA fatty acid composition, represented by an increased proportion of saturated fatty acids (P < 0.05) and a decreased proportion of n-3 PUFA (P < 0.01). Ectopic lipid deposition in the kidneys of HHTg rats-triglycerides (+30%) and cholesterol (+10%)-was associated with markedly elevated microalbuminuria as ageing increased, despite the absence of microalbuminuria at the young age of 3 months in these animals. According to targeted proteomic analysis, 3-month-old HHTg rats (in comparison to age-matched controls) exhibited increased urinary secretion of proinflammatory parameters (MCP-1, IL-6, IL-8, P < 0.01) and decreased urinary secretion of epidermal growth factor (EGF, P < 0.01) before manifestation of microalbuminuria. Elevation in the urinary secretion of inflammatory cytokines can be affected by increased relative expression of MCP-1 in the renal cortex (P < 0.05). Conclusions: Our results confirm dyslipidemia and ectopic lipid accumulation to be key contributors in the development of metabolic syndrome-associated renal dysfunction. Assessing urinary secretion of proinflammatory cytokines and epidermal growth factor can help in detecting early development of metabolic syndrome-associated renal dysfunction.
Keywords: nemoci ledvin; Animals; Cytokines; Rats, Wistar; biologické markery; albuminurie; Biomarkers; Predictive Value of Tests; lipidy; cytokiny; prediktivní hodnota testů; časové faktory; Metabolic Syndrome; Time Factors; Urinalysis; Inflammation Mediators; proteomika; Lipids; metabolický syndrom; Kidney Diseases; časná diagnóza; epidermální růstový faktor; Proteomics; Male; modely nemocí na zvířatech; Albuminuria; analýza moči; Rats, Transgenic; Disease Models, Animal; Early Diagnosis; Hypertriglyceridemia; mediátory zánětu; zvířata; mužské pohlaví; Epidermal Growth Factor; potkani transgenní; hypertriglyceridemie; potkani Wistar